2015
DOI: 10.1016/s0924-9338(15)31988-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-thyroid Antibodies in Bipolar Disorder

Abstract: Background: Dysfunction of the hypothalamus-pituitary-thyroid axis has been shown to play a role in the pathophysiology of bipolar disorder. Autoimmune thyroiditis is the most common cause of thyroid function alteration. Thus, auto-immune thyroiditis is likely associated with bipolar disorder. It might influence its course, prognosis and/or management. Objective: To study the prevalence of positive anti-thyroid antibodies in patients with bipolar disorder and to examine the prognostic and the therapeutic impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…46,47 These findings suggest that thyroid autoantibodies, especially anti-TPOs) could have potential utility as a biomarker for hypothyroidism in patients taking quetiapine and may even affect prognosis. 7 Another plausible mechanism for the decrease of thyroid hormones during quetiapine treatment is competitive metabolism of thyroid hormones and quetiapine by uridine 5 -diphosphoglucurosyltransferase. 33 Nonetheless, direct action of quetiapine on the hypothalamopituitary axis cannot also be excluded, although TSH levels have been reported to remain unaffected in context of decrease in thyroid hormones in some studies (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46,47 These findings suggest that thyroid autoantibodies, especially anti-TPOs) could have potential utility as a biomarker for hypothyroidism in patients taking quetiapine and may even affect prognosis. 7 Another plausible mechanism for the decrease of thyroid hormones during quetiapine treatment is competitive metabolism of thyroid hormones and quetiapine by uridine 5 -diphosphoglucurosyltransferase. 33 Nonetheless, direct action of quetiapine on the hypothalamopituitary axis cannot also be excluded, although TSH levels have been reported to remain unaffected in context of decrease in thyroid hormones in some studies (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…These factors may include the nature of the mental illness, sex, age group, duration of treatment, positive antithyroperoxidase antibodies (anti-TPOs) and whether quetiapine was used as monotherapy or in combination with other drugs. [5][6][7] It is also important to highlight that the drug manufacturer reported that quetiapine was associated with a dose-related decrease in TT4 and FT4. However, the underlying mechanism was not mentioned.…”
mentioning
confidence: 99%